An eco-friendly, low-power charge storage device from bio-tolerable nano cerium oxide electrodes for bioelectrical and biomedical applications. (23rd February 2018) - Dubey, Amarish; Jangir, Himanshi; Pandey, Mohit; Dubey, Mayank Manjul; Verma, Shourya; Roy, Manas; Singh, Sushil Kumar; Philip, Deepu; Sarkar, Sabyasachi; Das, Mainak
Abstract: Objective . A growing demand exists for eco-friendly, low-power charge storage devices for both biomedical and neuro-electrical applications, with a push towards the use of biocompatible and bio-tolerable electrodes and eco-friendly electrolytes that could be easily integrated with wearable electronics. Approach . One of the promising bio-tolerable, biomedical materials is nano cerium oxide, which finds wide applications in biology and medicine, namely spinal cord injury, radiotherapy, cardio-protection, etc. Here, nano cerium oxide was used as an electrode material to test whether such a bio-tolerable material could be used in bioelectrical and neuro-electrical applications. Main results . We developed a symmetric charge storage device using nano-ceria electrodes coated with fructose (a fruit sugar that is neutral to diabetes patients). This device attains a potential window of +0.8 V to −0.8 V in the presence of an aqueous electrolyte, Na2 SO4, which is an eco-friendly electrolyte. The device retains 85% of the specific capacitance (∼350 F g −1 ) and peak current density of 12 mA cm −2 after completion of 10 000 cycles, thus highlighting the stability of the newly developed device. Further, the device could be used to operate DC fans and other solid state electronic devices. The CeO2 electrode was tested in biologically relevant fluids, namely phosphate buffered saline and Leibovitz (L-15) medium, and found to be functioning and stable. Significance . Bio-tolerable nano cerium oxide electrodes could find new and innovative applications in bio-electronics, electro-therapy, neuro-electronics, charge storage and wearable electronics.